Long Non-Coding RNA-TMPO-AS1 as ceRNA Binding to let-7c-5p Upregulates STRIP2 Expression and Predicts Poor Prognosis in Lung Adenocarcinoma - Wang, Juan; Yuan, Yixiao; Tang, Lin; Zhai, Haoqing; Zhang, Dahang; Duan, Lincan; Jiang, Xiulin; Li, Chen (Frontiers in Oncology, 2022)
This manuscript revealed a significantly increased expression of mRNA and protein of STRIP2 in lung adenocarcinoma compared with the adjacent normal tissues. GEO and Kaplan-Meier plotter databases showed higher STRIP2 expression level was correlated with poor prognosis survival of LUAD. Moreover, Cox regression analysis suggested that a higher STRIP2 level served as an independent risk factor in predicting deteriorative OS for LUAD patients. SsGSEA results showed STRIP2 expression level was positively correlated with infiltrating levels of Th2 cells in LUAD. At last, GO analysis indicated the biological processes were enriched in nuclear division and positive regulation of cell cycle. KEGG signaling pathway analysis showed STRIP2 was correlated with MAPK signaling pathway and TNF signaling pathway. GSEA database showed that STRIP2 was positively associated with the epithelial mesenchymal transition, cell cycle and TNF signaling pathway. Qrt-PCR assay show that STRIP2 was upregulated in LUAD cells lines. Knockdown of STRIP2 inhibited cell proliferation and migration in LUAD. Moreover importantly, we confirmed that the TMPO-AS1/let-7c-5p/STRIP2 network regulates STRIP2 overexpression in LUAD and is associated with poor prognosis. Conclusion Our finding indicated that STRIP2 acted as a crucial oncogene in LUAD, and correlated with unfavorable survival as well as tumor infiltration inflation.